Predictive analytics for human resources - Fitz-enz, Jac.; Mattox, John, 1971- (Hoboken, New Jersey : Wiley, 2014)
"Create and run a human resource analytics project with confidenceFor any human resource professional that wants to harness the power of analytics, this essential resource answers the questions: "Where do I start?" and "What tools are available?" Predictive Analytics for Human Resources is designed to answer these and other vital questions. The book explains the basics of every business--the vision, the brand, and the culture, and shows how predictive analytics supports them. The authors put the focus on the fundamentals of predictability and include a framework of logical questions to help set up an analytic program or project, then follow up by offering a clear explanation of statistical applications.Predictive Analytics for Human Resources is a how-to guide filled with practical and targeted advice. The book starts with the basic idea of engaging in predictive analytics and walks through case simulations showing statistical examples. In addition, this important resource addresses the topics of internal coaching, mentoring, and sponsoring and includes information on how to recruit a sponsor. In the book, you'll find: A comprehensive guide to developing and implementing a human resource analytics project Illustrative examples that show how to go to market, develop a leadership model, and link it to financial targets through causal modeling Explanations of the ten steps required in building an analytics function How to add value through analysis of systems such as staffing, training, and retention For anyone who wants to launch an analytics project or program for HR, this complete guide provides the information and instruction to get started the right way"--
"Predictive Analytics for Human Resources is a comprehensive guide to developing and implementing a human resource analytics project. The book starts with the basic idea of engaging in predictive analytics and walks through case simulations showing statistical examples. In addition, it addresses the topics of internal coaching, mentoring, and sponsoring and includes information on how to recruit a sponsor"--
Includes index.
Keywords: Personnel management; Human capital -- Management; Decision making; BUSINESS & ECONOMICS / Decision-Making & Problem Solving